A Benziodoxole-Based Hypervalent Iodine(III) Compound Functioning as a Peptide Coupling Reagent - Qiu, Li-Jun; Liu, Dan; Zheng, Ke; Zhang, Ming-Tao; Zhang, Chi (Frontiers in Chemistry, 2020)
1-Benzoyloxy-1,2-benziodoxol-3-(1H)-one (IBA-OBz), a readily available and bench stable benziodoxole-based iodine(III) reagent, can be employed for the synthesis of dipeptides from various standard and sterically hindered amino acids in the presence of (4-MeOC6H4)3P. The combined system of IBA-OBz/(4-MeOC6H4)3P is also successfully applied to the solid-phase peptide synthesis and a pentapeptide leu-enkephalin in unprotected form has been synthesized. Density functional theory calculations reveal that the rate-limiting step is nucleophilic attack of 4-dimethylaminopyridine (DMAP) onto IBA-OBz.